Pengaruh Konsentrasi dan Frekuensi Pemberian Pupuk Organik Cair Terhadap Pertumbuhan Tanaman dan Produksi Sawi Samhong (Brassica juncea L.) - Rehatta, Herman; Marasabessy, Dessy A; Gea, Meiman Sederhana (Universitas Pattimura, 2024)
In mustard cultivtion, the right combination of the concentration of liquid organic fertilizer given through the leaves and the frequency of application are factors that can optimize growth and yield. This research aimed to test the effectiveness of the concentration and frequency of NASA liquid organic fertilizer on the growth and yield of Samhong mustard (Brassica juncea L.). The research was carried out in the greenhouse of the Faculty of Agriculture, Pattimura University, Ambon. This research was conducted as an experiment using a Randomized Block Design with 2 factors. The first factor was the concentration of NASA liquid organic fertilizer which consisted of 4 levels, namely: concentration of 0 mL/L of water (without giving POC); 4 mL/L of water; 8 mL/ mL/L of water; and 12 mL/L of water. The second factor was the frequency of fertilizer application which consists of 3 levels, namely 6 times, 3 times and 2 times of application. There were 12 treatment combinations, with 3 replications, so there were 36 experimental units. The research results showed that the concentration of NASA liquid organic fertilizer had a very significant effect on plant height, number of leaves, leaf area, plant fresh weight, plant dry weight and root dry weight. A concentration of 8 mL/L of water was the best concentration for plant fresh weight, namely 323.89 g. For the treatment of frequency of application, there was a very significant effect on the number of leaves, leaf area, plant fresh weight, plant dry weight and root dry weight, with a frequency of 3 applications being the best frequency for the growth and yield of Samhong mustard greens. The interaction between NASA liquid organic fertilizer concentration and application frequency did not significantly effect all observed variables.